The new American workplace - O'Toole, James 1945-; Lawler, Edward E. III. 1938- (Palgrave Macmillan, 2006)
Redefines the state of the nation's workplace in the current generation, citing significant changes to such elements as the role of working women, the pervasiveness of outsourcing, and a meteoric rise in worker competitiveness.
Contents: I: Work in America -- II: Changes in the American workplace -- The nature of organizations -- The work itself -- The employment relationship -- III: Consequences for the American worker -- Careers -- Work/life balance -- Health and safety -- Job and life satisfaction -- Performance pressure -- Compensation -- Employee "voice" -- Training and development -- Community and commitment -- Winners and losers -- IV: Choices and future directions -- Organizations and competitiveness -- Public policy -- Individuals -- V: Future of the American workplace. - Includes bibliographical references and index
Keywords: Quality of work life -- United States; Labor market -- United States; Labor supply -- United States; Industrial organization -- United States; Industrial sociology -- United States; Industriesoziologie; Lebensqualität; Arbeitsmarkt; USA